The Possibilities of Dark Tourism and Ways to Develop it in the Kurdistan Region of Iraq - Rashid, Shirwan O.; Fattah Al-Saffar, Bahri S.; Saleh, Peyman M. (Mitanni Journal of Humanitarian Sciences, 2023)
This research seeks to know the extent to which private banks are aware of the dimensions of internal marketing and their impact on the banks’ performance in order to be distinguished in marketing, and that the function of internal marketing is concerned with employees and considering them as internal customers in an internal market. The impact of the internal marketing dimensions has been tested and evaluated as independent variables, and marketing excellence as a dependent variable using the statistical program ( (SPSS), and a questionnaire form was distributed to obtain data, and its size was (70) individuals from the employees of (Bikhal Bank). The results of the research showed that there is a positive moral correlation between the dimensions of internal marketing and marketing excellence, as well as the existence of an effect of the dimensions of internal marketing and marketing excellence. One of the most important recommendations reached by the research is (the necessity of activating development and training processes for all employees in the bank, including its importance in achieving marketing excellence and its positive impact on the bank’s performance, and that training allows employees to participate in information, ideas, and problems).